EGMR 21353/93 vom 16. Dezember 1997 , CASE OF CAMENZIND v. SWITZERLAND - Hudoc Ch (1997)
No violation of Art. 8;Preliminary objection rejected;Violation of Art. 13+8;Non-pecuniary damage - finding of violation sufficient;Costs and expenses partial award - Convention proceedings; Violation: 13+8;13;8; No violation: 8